Best Way to Detect Breast Cancer by UsingMachine Learning Algorithms - Arabi Hamdo, Nahla (Iraqi Journal of Science, 2023)
Breast cancer is the second deadliest disease infected women worldwide. For thisreason the early detection is one of the most essential stop to overcomeit dependingonautomatic devices like artificial intelligent. Medical applications of machine learningalgorithmsare mostly based on their ability to handle classification problems,including classifications of illnesses or to estimate prognosis. Before machinelearningis applied for diagnosis, it must be trained first. The research methodologywhich isdetermines differentofmachine learning algorithms,such as Random tree,ID3, CART, SMO, C4.5 and Naive Bayesto finds the best training algorithm result.The contribution of this research is test the data set with missing value and withoutmissing value, where the missing value is one attribute is missing from one samplefor data set. The test result is show SMO is the best algorithm, especiallywhen theresearch removes the samples that contained the missing value.